Confluent flow impacts of flood extremes in the middle Yellow River. (4th September 2015) - He, Hongming; Tian, Yong Q.; Mu, Xingmin; Zhou, Jie; Li, Zhanbin; Cheng, Nannan; Zhang, Qingle; Keo, Soksamnang; Oeurng, Chantha
Abstract: Flood disaster has been one of the most frequent and devastating forms in middle Yellow River, China. Huge flood events transport sediments from upstream to downstream, and lead to changes of river morphology, such as river bed slope, channel roughness, and flood routing process. Flood disasters in the middle Yellow River were constantly caused by backwater effects due to multiple river stream confluence effects. The study aims to investigate confluent flood flow effects on flood routing processes, river morphology, and human activities based on a proposed flood flow model. The proposed model is constructed through coupling hydraulic equations, artificial intelligence neural network and probability theory. Flood frequency analysis is coupled with studies of hydrological routing processes that reduce the flood capacity of the rivers. Flood routing to the confluence were simulated using kinematic wave theory. Case studies have been carried out through field work and model simulation during the past years. Findings are achieved as followings. Firstly, flood frequency at the confluence implies that the confluent extreme flood occurs more frequently in the main streams than that in the tributaries due to influential intensity of East-Asian summer monsoon. Secondly, river morphology was altered partly due to complex flood routing processes in the middle Yellow River under the operation of Sanmenxia Reservoir. The alternated river channels changed the boundary conditions of flood routing, especially for backwater. Bed slopes have greater impacts on flood routing process than roughness does when there is larger flood flow. Finally, the evolution process of the sediment transportation is closely linked with the operations of the Sanmenxia Reservoir.